A study on the effectiveness of promotional mix towards FELDA trading product / Nor Amira Ayon - Ayon, Nor Amira (Faculty of Business and Management, 2011)
Promotion is very important to the organization whether it is profit or non-profit organization. This is because a good promotion may promise a good feedback from public and also the potential members towards the services that they offered to public especially for Muslims. This study focuses on ‘A study on effectiveness of promotional mix towards Felda Trading product’. The objective is to determine the promotion tools that have given the greatest exposure to Felda Trading Sdn Bhd and also to establish the relationship between promotional mix and the effectiveness of promotional tools that had been implemented by Felda Trading. The sampling technique that has been used was the non-probability sampling where 80 respondents were chosen by the researcher using sample random sampling from Felda Trading database to answers the questionnaires. Besides that, correlation was conducted to determine the correlation between the promotional mix and the effectiveness of promotional tools. Findings in the study showed that public relation and sales promotion has given the big impact to Felda Trading and it is most effective promotional tools. Meanwhile, the result that direct marketing is the in effective